Design Methodology for a Floating Offshore Wind Turbine Large-Scale Outdoor Prototype - Fontanella, Alessandro; Taruffi, Federico; Muggiasca, Sara; Belloli, Marco (Volume 10: Ocean Renewable Energy, 2019)
This paper discusses the methodology introduced by the authors to design a large-scale wind turbine model starting from the DTU 10MW RWT. The wind turbine will be coupled with the model of a multi-purpose floating structure, designed within the EU H2020 Blue Growth Farm project, and it will be deployed at the Natural Ocean Engineering Laboratory (NOEL). In this paper the different strategies used to design the wind turbine model rotor, tower and nacelle are discussed, focusing on how it has been possible to reproduce the full-scale system aero-elastic response while ensuring the same functionalities of a real wind turbine.